Scale variance minimization for unsupervised domain adaptation in image segmentation. (April 2021) - Guan, Dayan; Huang, Jiaxing; Lu, Shijian; Xiao, Aoran
Highlights: Scale-invariance constraint preserves semantic structures of images. Scale variance minimization ensures optimal unsupervised domain adaptation. Proposed method is complementary to most existing domain adaptation techniques. Superior performance has been achieved comparing with the state-of-the-art. Abstract: We focus on unsupervised domain adaptation (UDA) in image segmentation. Existing works address this challenge largely by aligning inter-domain representations, which may lead over-alignment that impairs the semantic structures of images and further target-domain segmentation performance. We design a scale variance minimization (SVMin) method by enforcing the intra-image semantic structure consistency in the target domain. Specifically, SVMin leverages an intrinsic property that simple scale transformation has little effect on the semantic structures of images. It thus introduces certain supervision in the target domain by imposing a scale-invariance constraint while learning to segment an image and its scale-transformation concurrently. Additionally, SVMin is complementary to most existing UDA techniques and can be easily incorporated with consistent performance boost but little extra parameters. Extensive experiments show that our method achieves superior domain adaptive segmentation performance as compared with the state-of-the-art. Preliminary studies show that SVMin can be easily adapted for UDA-based image classification.